THE IMPACT OF CLIMATIC CONDITIONS ON ARCHAEOLOGICAL SITES - Aytmuratova Aynur Polatbaevna (Web of Journals Publishing, 2025)
The article presents the influence of climatic conditions on the object of archaeological and cultural heritage in general based on terms. The results of the influence of climatic conditions observed at the Toprakkala and Akchahankala monuments are presented. From this, the last ten-year report on climate monitoring work in the area where exactly two objects are located was studied.
Keywords: Archaeology, climate, object, thermoplasticism, corrosion, karst effect, salt crystallization, hydrometeorology, termite.